Power, double binds, and transcendence in the mentoring relationship: a transpersonal perspective. (4th June 2007) - Elmes, Michael B.; Smith, Charles H.
This paper describes some of the problems that can arise in a mentoring relationship a relationship that is both power dependent and helping. It draws on Bateson's theory of double binds to consider ways by which mentors sometimes try to maintain a power imbalance in the mentoring relationship and how proteges try to resist that imbalance. It draws upon the spiritual insights from various wisdom traditions to offer ways to avoid and transcend those binds. The paper concludes with a short case to illustrate the key ideas from the paper. It calls for more research on the micro-dynamics mentoring relationships using clinical research methods.